Asthma severity and atopy: how clear is the relationship?. Issue 5 (27th January 2006) - Carroll, W D; Lenney, W; Child, F; Strange, R C; Jones, P W; Whyte, M K; Primhak, R A; Fryer, A A
Abstract : Background: The relationship between asthma severity and atopy is complex. Many studies have failed to show significant relationships between clinical severity or lung function and markers of atopic sensitisation. Aim: To determine whether increasing asthma severity is related to atopic sensitisation in a population of children with asthma. Methods: A total of 400 children (7–18 years) with asthma were recruited as part of a multicentre study of the genetics of asthma. Detailed phenotypic data were collected on all participants. Associations between measures of asthma severity and atopic sensitisation were sought using multilevel models allowing variation at the individual and family level. Results: Children recruited to the study had a range of asthma severities, with just over a third having mild persistent asthma. The logarithm of total serum IgE was associated with increased asthma severity score, decreased FEV1, increased airways obstruction, risk of hospital admission, and inhaled steroid use. Increasing skin prick test reactivity to a panel of seven aeroallergens was associated with increased risk of hospital admission, use of an inhaled steroid, and airways obstruction. The results remained highly significant after corrections for age, gender, and birth order. Conclusions: In children with asthma, increasing atopy is associated with increasing asthma severity. However, the relationships between asthma severity and skin prick tests, and asthma severity and total serum IgE values, appear subtly different.